Primary hemostatic disorders drive early and late major bleedings of patients with atrial fibrillation after transcatheter aortic valve replacement. (14th October 2021) - Matsushita, K; Marchandot, B; Hess, S; Kibler, M; Sato, C; Heger, J; Truong, D P; Trimaille, A; Sattler, L; Grunebaum, L; Reydel, A; Jesel, L; et al.
Abstract: Introduction: Patients with atrial fibrillation (AF) are likely to have multiple co-morbidities and receive anticoagulants after TAVR, which lead to a poor prognosis including bleeding events. Closure time adenosine diphosphate (CT-ADP) is a primary hemostasis point-of-care test used as a surrogate marker of high molecular weight (HMW) multimers defect of Von Willebrand factor (VWF). Our prior studies suggest that prolongation of CT-ADP (>180 seconds) after TAVR is a major determinant of early and late major/life-threatening bleeding complications (MLBCs). Purpose: To evaluate the impact of post-procedural CT-ADP >180sec on bleeding events in AF patients. Methods: We included 878 patients from our prospective TAVR registry between 2010 and 2019. Bleeding complications were assessed according to the VARC-2 (Valve Academic Research Consortium-2) criteria. Major adverse cardiac and cerebrovascular events (MACCE) was defined as a composite of all-cause death, myocardial infarction, stroke, and heart failure hospitalization within 1-year after TAVR. Ongoing primary haemostasis disorder was defined by post-procedure CT-ADP >180sec. Primary endpoint was the occurrence of MLBCs during the first year and the second endpoint was 1-year MACCE. Results: Patients with AF had a higher incidence of all-cause mortality (15% vs. 8%, p=0.002), MACCE (29% vs. 20%, p=0.002), and MLBCs (20% vs. 12%, p=0.001) within 1-year compared to non-AF patients. When the cohort was split into 4 subgroups according to AF and CT-ADP >180sec, patients with AF and CT-ADP >180sec had the highest risk of MLBCs (log-rank test; p<0.001) (Figure). Multivariate Cox regression analysis confirmed that the patients with AF and CT-ADP >180sec had 4.6-fold higher risk of MLBCs within 1 year compared to non-AF patients with CT-ADP ≤180sec (hazard ratio: 4.60; 95% confidence interval: 2.18 - 9.68; p<0.001). Conclusion: Among TAVR patients, AF with post-procedural CT-ADP >180 sec was identified as a strong independent predictor of MLBCs at 1-year follow-up. Our study suggest that persistent primary haemostasis disorders contribute to a higher risk of bleeding events particularly in AF patients and may be considered for a tailored and risk-adjusted antithrombotic therapy after TAVR. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Dr Matsushita received a grant from Edwards Lifesciences.